Depressed left and right ventricular cardiac output in fetuses of diabetic mothers. Issue 1 (March 2018) - Winter, Jennifer; Kulkarni, Aparna; Craft, Mary; Li, Ling; Hornberger, Lisa K; Danford, David A; Kutty, Shelby
Abstract : Introduction: We compared right and left ventricular cardiac output (RVCO and LVCO) in fetuses of diabetic mothers (FDM) with a large normal cohort. Methods: We prospectively enrolled 264 normal fetuses and 30 FDM. Fetal CO parameters such as semilunar valve velocity time integrals (AVVTI, PVVTI), ventricular outflow diameters (LVOTD, RVOTD) and stroke volumes (AVSV, PVSV) were measured, and LVCO and RVCO were calculated. These were normalized using non-linear regression to estimated fetal weight (EFW) to provide means and standard deviations. Among FDMs, mean Z scores and 95% confidence limits (CL) were calculated and compared to zero. Results: LVCO, RVCO and parameters they were calculated from, increased predictably and non-linearly with increasing EFW. In FDM, LVCO was depressed (mean Z −1.679, 95% CL −2.404, −0.955, P  < 0.001), and AVVTI, LVOTD and AVSV were significantly lower than normal. Similarly, RVCO (mean Z  = −1.119, CL −1.839, −0.400, P  = 0.003), RVOTD (mean −2.085, CL −3.077, −1.093, P  < 0.001) and PVSV (mean −1.184, CL −1.921, −0.446, P  = 0.003) were lower than normal, however, PVVTI was not different (mean Z 0.078, CL −0.552, +0.707, P  = 0.803). Conclusion: Normal biventricular stroke volumes and outputs follow a non-linear regression with EFW. FDM have significantly lower right and left heart stroke volumes and outputs for weight than do normal fetuses.